2019
DOI: 10.1590/abd1806-4841.20198170
|View full text |Cite
|
Sign up to set email alerts
|

Nail psoriasis treated with intralesional methotrexate infiltration

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by recurrent events. Its prevalence around the world is approximately 1-3%. 1,2 It´s estimated that 80-90% of patients with psoriasis will present with nail disorders throughout their lives. 2,3 Studies have shown that nail psoriasis is the causes a significant social problem, often associated with pain. 2 Different therapeutic options can be found for nail psoriasis, which include topical medication, intralesional treatment, systemic therapy, conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Triamcinolone acetonide was the most commonly injected drug in nail psoriasis. 3 Intralesional injection of methotrexate in psoriatic nails was addressed in individual case reports 4,5 and few large-scale studies. 2,3 Methotrexate is a folic acid analog, responsible for inhibiting the synthesis of DNA with a direct toxic effect on keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triamcinolone acetonide was the most commonly injected drug in nail psoriasis. 3 Intralesional injection of methotrexate in psoriatic nails was addressed in individual case reports 4,5 and few large-scale studies. 2,3 Methotrexate is a folic acid analog, responsible for inhibiting the synthesis of DNA with a direct toxic effect on keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional injection of methotrexate has been successfully used in the treatment of recalcitrant nail psoriasis in previous reports. [2][3][4][5] The local injection of the drug may avoid the need for systemic treatment and help deliver the drug in high concentrations into the nail matrix. 3 Although intramatricial injection is a safe and effective modality, pain is still the major side effect which can greatly decrease patient compliance, especially in patients with multiple digits involvement.…”
mentioning
confidence: 99%
“…Mokni and Duarte reported progressive improvement in nail dystrophy with intralesional MTX injection in nail psoriasis [9,10]. Mittal et al reported that intralesional methotrexate and corticosteroid injections show similar efficacy in nail psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review shows that intralesional MTX has been successfully used for several indications with no complications reported (Duarte, Carneiro, Murari, & Jesus, ). Unlike oral MXT, topical preparations of the drug, that was adapted for the treatment of localized lesions, showed nonsignificant related hepatotoxic and hematologic adverse effects (Sutton, Swinehart, Cato, & Kaplan, ).…”
Section: Discussionmentioning
confidence: 99%